Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Asymmetric responses of ecosystem productivity to rainfall anomalies vary inversely with mean annual rainfall over the conterminous United States - Amen Al‐Yaari; Jean‐Pierre Wigneron; Philippe Ciais; Markus Reichstein; Ashley Ballantyne; Jerome Ogée; Agnès Ducharne; Jennifer J. Swenson; Frédéric Frappart; Lei Fan; Lisa Wingate; Xiaojun Li; et al. (Global Change Biology, 2020)
The CONterminous United States (CONUS) presents a large range of climate conditions and biomes where terrestrial primary productivity and its inter‐annual variability are controlled regionally by rainfall and/or temperature. Here, the response of ecosystem productivity to those climate variables was investigated across different biomes from 2010 to 2018 using three climate datasets of precipitation, air temperature or drought severity, combined with several proxies of ecosystem productivity: a remote sensing product of aboveground biomass, an net primary productivity (NPP) remote sensing product, an NPP model‐based product and four gross primary productivity products. We used an asymmetry index (AI) where positive AI indicates a greater increase of ecosystem productivity in wet years compared to the decline in dry years, and negative AI indicates a greater decline of ecosystem productivity in dry years compared to the increase in wet years. We found consistent spatial patterns of AI across the CONUS for the different products, with negative asymmetries over the Great Plains and positive asymmetries over the southwestern CONUS. Shrubs and, to a lesser extent, evergreen forests show a persistent positive asymmetry, whilst (natural) grasslands appear to have transitioned from positive to negative anomalies during the last decade. The general tendency of dominant negative asymmetry response for ecosystem productivity across the CONUS appears to be influenced by the negative asymmetry of precipitation anomalies. AI was found to be a function of mean rainfall: more positive AIs were found in dry areas where plants are adapted to drought and take advantage of rainfall pulses, and more negative AIs were found in wet areas, with a threshold delineating the two regimes corresponding to a mean annual rainfall of 200–400 mm/year.

A dynamic leaf gas‐exchange strategy is conserved in woody plants under changing ambient CO 2 : evidence from carbon isotope discrimination in paleo and CO 2 enrichment studies - Steven L. Voelker; J. Renée Brooks; Frederick C. Meinzer; Rebecca Anderson; Martin K.‐F. Bader; Giovanna Battipaglia; Katie M. Becklin; David Beerling; Didier Bert; Julio L. Betancourt; Todd E. Dawson; Jean‐Christophe Domec; et al. (Global Change Biology, 2016)
Rising atmospheric [CO 2 ], c a , is expected to affect stomatal regulation of leaf gas‐exchange of woody plants, thus influencing energy fluxes as well as carbon (C), water, and nutrient cycling of forests. Researchers have proposed various strategies for stomatal regulation of leaf gas‐exchange that include maintaining a constant leaf internal [CO 2 ], c i , a constant drawdown in CO 2 ( c a − c i ), and a constant c i / c a . These strategies can result in drastically different consequences for leaf gas‐exchange. The accuracy of Earth systems models depends in part on assumptions about generalizable patterns in leaf gas‐exchange responses to varying c a . The concept of optimal stomatal behavior, exemplified by woody plants shifting along a continuum of these strategies, provides a unifying framework for understanding leaf gas‐exchange responses to c a . To assess leaf gas‐exchange regulation strategies, we analyzed patterns in c i inferred from studies reporting C stable isotope ratios (δ 13 C) or photosynthetic discrimination (∆) in woody angiosperms and gymnosperms that grew across a range of c a spanning at least 100 ppm. Our results suggest that much of the c a ‐induced changes in c i / c a occurred across c a spanning 200 to 400 ppm. These patterns imply that c a − c i will eventually approach a constant level at high c a because assimilation rates will reach a maximum and stomatal conductance of each species should be constrained to some minimum level. These analyses are not consistent with canalization toward any single strategy, particularly maintaining a constant c i . Rather, the results are consistent with the existence of a broadly conserved pattern of stomatal optimization in woody angiosperms and gymnosperms. This results in trees being profligate water users at low c a , when additional water loss is small for each unit of C gain, and increasingly water‐conservative at high c a , when photosystems are saturated and water loss is large for each unit C gain.

Reconciling the optimal and empirical approaches to modelling stomatal conductance - Belinda E. Medlyn; Remko A. Duursma; Derek Eamus; David S. Ellsworth; I. Colin Prentice; Craig V. M. Barton; Kristine Y. Crous; Paolo de Angelis; Michael Freeman; Lisa Wingate (Global Change Biology, 2012)

Carbon isotope evidence for recent climate‐related enhancement of CO 2 assimilation and peat accumulation rates in Antarctica - Jessica Royles; Jérôme Ogée; Lisa Wingate; Dominic A. Hodgson; Peter Convey; Howard Griffiths (Global Change Biology, 2012)
Signy Island, maritime Antarctic, lies within the region of the Southern Hemisphere that is currently experiencing the most rapid rates of environmental change. In this study, peat cores up to 2 m in depth from four moss banks on Signy Island were used to reconstruct changes in moss growth and climatic characteristics over the late Holocene. Measurements included radiocarbon dating (to determine peat accumulation rates) and stable carbon isotope composition of moss cellulose (to estimate photosynthetic limitation by CO 2 supply and model CO 2 assimilation rate). For at least one intensively 14 C‐dated Chorisodontium aciphyllum moss peat bank, the vertical accumulation rate of peat was 3.9 mm yr −1 over the last 30 years. Before the industrial revolution, rates of peat accumulation in all cores were much lower, at around 0.6–1 mm yr −1 . Carbon‐13 discrimination (Δ), corrected for background and anthropogenic source inputs, was used to develop a predictive model for CO 2 assimilation. Between 1680 and 1900, there had been a gradual increase in Δ, and hence assimilation rate. Since 1800, assimilation has also been stimulated by the changes in atmospheric CO 2 concentration, but a recent decline in Δ (over the past 50–100 years) can perhaps be attributed to documented changes in temperature and/or precipitation. The overall increase in CO 2 assimilation rate ( 13 C proxy) and enhanced C accumulation ( 14 C proxy) are consistent with warmer and wetter conditions currently generating higher growth rates than at any time in the past three millennia, with the decline in Δ perhaps compensated by a longer growing season.

Strong seasonal disequilibrium measured between the oxygen isotope signals of leaf and soil CO 2 exchange - LISA WINGATE; JÉRÔME OGÉE; RÉGIS BURLETT; ALEXANDRE BOSC (Global Change Biology, 2010)
The oxygen isotope composition ( δ 18 O) of atmospheric CO 2 is among a very limited number of tools available to constrain estimates of the biospheric gross CO 2 fluxes, photosynthesis and respiration at large scales. However, the accuracy of the partitioning strongly depends on the extent of isotopic disequilibrium between the signals carried by these two gross fluxes. Chamber‐based field measurements of total CO 2 and CO 18 O fluxes from foliage and soil can help evaluate and refine our models of isotopic fractionation by plants and soils and validate the extent and pattern of isotopic disequilibrium within terrestrial ecosystems. Owing to sampling limitations in the past, such measurements have been very rare and covered only a few days. In this study, we coupled automated branch and soil chambers with tuneable diode laser absorption spectroscopy techniques to continuously capture the δ 18 O signals of foliage and soil CO 2 exchange in a Pinus pinaster Aït forest in France. Over the growing season, we observed a seasonally persistent isotopic disequilibrium between the δ 18 O signatures of net CO 2 fluxes from leaves and soils, except during rain events when the isotopic imbalance became temporarily weaker. Variations in the δ 18 O of CO 2 exchanged between leaves, soil and the atmosphere were well explained by theory describing changes in the oxygen isotope composition of ecosystem water pools in response to changes in leaf transpiration and soil evaporation.

Biotic and abiotic factors affecting the δ 13 C of soil respired CO 2 in a Mediterranean oak woodland† - Kadmiel Maseyk; Lisa Wingate; Ulli Seibt; Jaleh Ghashghaie; Camille Bathellier; Pedro Almeida; Raquel Lobo de Vale; Joao S. Pereira; Dan Yakir; Maurizio Mencuccini (Isotopes in Environmental and Health Studies, 2009)

Evaporation and carbonic anhydrase activity recorded in oxygen isotope signatures of net CO 2 fluxes from a Mediterranean soil - LISA WINGATE; ULLI SEIBT; KADMIEL MASEYK; JÉRÔME OGÉE; PEDRO ALMEIDA; DAN YAKIR; JOAO S. PEREIRA; MAURIZIO MENCUCCINI (Global Change Biology, 2008)
The oxygen stable isotope composition ( δ 18 O) of CO 2 is a valuable tool for studying the gas exchange between terrestrial ecosystems and the atmosphere. In the soil, it records the isotopic signal of water pools subjected to precipitation and evaporation events. The δ 18 O of the surface soil net CO 2 flux is dominated by the physical processes of diffusion of CO 2 into and out of the soil and the chemical reactions during CO 2 –H 2 O equilibration. Catalytic reactions by the enzyme carbonic anhydrase, reducing CO 2 hydration times, have been proposed recently to explain field observations of the δ 18 O signatures of net soil CO 2 fluxes. How important these catalytic reactions are for accurately predicting large‐scale biosphere fluxes and partitioning net ecosystem fluxes is currently uncertain because of the lack of field data. In this study, we determined the δ 18 O signatures of net soil CO 2 fluxes from soil chamber measurements in a Mediterranean forest. Over the 3 days of measurements, the observed δ 18 O signatures of net soil CO 2 fluxes became progressively enriched with a well‐characterized diurnal cycle. Model simulations indicated that the δ 18 O signatures recorded the interplay of two effects: (1) progressive enrichment of water in the upper soil by evaporation, and (2) catalytic acceleration of the isotopic exchange between CO 2 and soil water, amplifying the contributions of ‘atmospheric invasion’ to net signatures. We conclude that there is a need for better understanding of the role of enzymatic reactions, and hence soil biology, in determining the contributions of soil fluxes to oxygen isotope signals in atmospheric CO 2 .